Simultaneous Estimation of Artemether and Lumefantrine by RP-HPLC Method Development in Pharmaceutical Tablet Dosage Form - Lekhana A M; Paul Richards M; Vishwanath BA (RGUHS Journal of Pharmaceutical Sciences)
Background Artemether and Lumefantrine are widely used antimalarial agents whose simultaneous quantification in tablet formulations is essential for quality control.Objectives To develop and validate a simple accurate and robust reverse-phase high-performance liquid chromatography RP-HPLC method for the simultaneous estimation of Artemether and Lumefantrine in tablet dosage forms.Methods Chromatographic analysis was performed using a Hypersil BDS C18 column 250times4.6 mm 5 mum with a mobile phase composed of a buffer and acetonitrile in a 5050 vv ratio. The pH was adjusted to 3.0 plusmn 0.6 using orthophosphoric acid. The flow rate was set at 1.5 mLmin and detection was performed at 215 nm. The method was validated in accordance with ICH guidelines for linearity accuracy precision and robustness.Results The retention times of Artemether and Lumefantrine were 2.464 and 6.236 minutes respectively. Linearity was observed over the concentration ranges of 4-24 mugmL for Artemether and 24-144 mugmL for Lumefantrine with correlation coefficients rsup2 exceeding 0.999. The method met the required criteria for accuracy precision and robustness.Conclusion The developed RP-HPLC method is direct reliable and reproducible. It is suitable for routine quality control analysis of Artemether and Lumefantrine in tablet formulations.